Progesterone Regulation of Milk Fat Globule Size Is VLDL Dependent - Argov-Argaman, Nurit; Raz, Chen; Roth, Zvi (Frontiers in Endocrinology, 2020)
Progesterone plays a pivotal role during mammogenesis and serves as an inhibitor of the secretory activation of mammary cells in the last days of gestation. However, its role during lactogenesis, in particular its involvement in lipid metabolism, and milk fat content and composition, is unknown. Here, we provide new evidence of progesterone's involvement in the regulation of milk fat globule (MFG) synthesis and secretion. Findings from both in vivo and in vitro studies indicated that the concentration and the direction (increase vs. decrease) of progesterone concentration to which the mammary epithelial cells (MECs) are exposed affect MFG size. This was found to be very-low-density lipoprotein (VLDL) dependent: in the presence of VLDL, the proportion of MEC with small lipid droplets (<1 μm) increased 2.4-fold, and the proportion of large lipid droplets (>1 μm) increased 4-fold; in the absence of VLDL, no differences were found. The findings add to our understanding of the mechanism underlying the regulation of MFG size and provide new evidence for progesterone's role in lipid metabolism in the mammary gland during lactogenesis. The fact that the size, synthesis, and composition of MFG are affected by the cyclic pattern of progesterone concentration in the circulation might have physiologically relevant consequences, in particular on milk as a nutritional source.